Desktop study on Novel Treatment techniques to treat industrial fertilizer effluent - Fortuin, Jordache (Department of Civil Engineering, 2019)
Fertilizer production is a massive global industry with the global consumption of the three main fertilizer nutrients, nitrogen, phosphate and potassium estimated at 187 million tonnes in 2016 with an anticipated annual growth of approximately 2% for the foreseeable future. In 2016 the global fertilizer market was estimated to have an overall market value of 141 billion US dollars. Fertilizer production produces significant liquid waste as process water used for the various separations, cleaning, emulsifying and dilution processes absorbs various nutrients and contaminants from these production processes. This liquid waste has characteristically high concentrations of nutrients derived from the base fertilizer, such as various dissolved phosphate compounds for phosphate-based fertilizer production or dissolved nitrogenous compounds for nitrogen based fertilizer production. These contaminants are inherently nutrients that could be recovered for beneficial re-use. The phosphate and potassium minerals used in fertilizer production are obtained from ores mined from the earth, thus the re-use of these mineral present particular significance when taking into accounting the declining global supply of these ores. Furthermore, if these liquid wastes are not disposed of correctly they can lead to detrimental environmental impacts such as eutrophication and ecological degradation in water courses. This study addresses this problem by presenting three novel treatment techniques to treat the liquid waste produced from a fertilizer production plant. A liquid waste sample obtained from a particular fertilizer production plant producing primarily nitrogen-based fertilizer is used as a design basis to evaluate the three presented treatment techniques. The techniques are evaluated based on their economic feasibility, technical feasibility and resource recovery ability. The three treatment techniques studied were the Sharon-Anammox bioreaction process, electrodialysis with struvite recovery process and combined forward-reverse osmosis process. The technical feasibility of the processes was primarily evaluated based on the effluent water quality from the treatment systems. The effluent quality index (EQI) was used as a comparative measure of the effluent quality of the processes. All three processes were found to perform inadequately from a technical feasibility perspective as demonstrated by the negative EQI values obtained for the processes. The Sharon-Anammox bioreaction process was found to perform poorly because its application is limited to treatment of waste streams containing high ammonia concentrations such as in conventional domestic waste. Therefore, the Sharon-Anammox process was not suited to the fertilizer effluent which also contained high nitrates, phosphates and total dissolved solids. The electrodialysis process performed poorly as it was unable to effectively remove the ammonium cations from the process water. The combined forward-reverse osmosis process performed poorly because a resource recovery step was not included to treat the concentrated waste stream discharged from the forward osmosis step of the process. It was identified that a similar struvite recovery step should be added to the combined forward-reverse osmosis process to improve the technical feasibility of the process and to provide the process with resource recovery capabilities. From an economic feasibility perspective, it was found that the addition of the struvite recovery setup to the electrodialysis process increased the capital costs of the process to between 300% and 500% of the other two options. However, with the omission of the struvite recovery setup the capital costs of all three processes were in a similar range.